2018
DOI: 10.5812/archneurosci.60507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synbiotic as an Adjuvant Therapy to Fluoxetine in Moderate Depression: A Randomized Multicenter Trial

Abstract: Background: Depression is a serious and burdensome disorder in modern societies, with lifetime prevalence of about 16%. Disturbed immune responses in the gut and immune-privileged sites including the central nervous system might occur subsequent to dysbiosis of gut microbiome. In this study we aimed at assessing the efficacy of 6 weeks synbiotic supplementation in the treatment of moderate depression in a double-blind, placebo-controlled, multi-center, and randomized trial. Methods: A total of 40 adult outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 17 publications
2
95
0
10
Order By: Relevance
“…The role of gut microbiota in anxiety, depression and the HPA axis has been studied through assessing the effects of prebiotics and probiotics administration in these conditions [57][58][59]. It has been reported that "germ-free" mice may have increased plasma levels of serotonin and tryptophan.…”
Section: Serotonin Pathway Involvement In Migraine Headache With a Fomentioning
confidence: 99%
“…The role of gut microbiota in anxiety, depression and the HPA axis has been studied through assessing the effects of prebiotics and probiotics administration in these conditions [57][58][59]. It has been reported that "germ-free" mice may have increased plasma levels of serotonin and tryptophan.…”
Section: Serotonin Pathway Involvement In Migraine Headache With a Fomentioning
confidence: 99%
“…However, MSPs may have higher potency in humans. In MDD patients, SSP (L. plantarum) did not reduce depression but improved cognition (Lew et al, 2018), whereas MSPs had repeatedly shown antidepressive efficacy (Akkasheh et al, 2016;Bambling et al, 2017;Ghorbani et al, 2018;Kazemi et al, 2019). MSPs often gave better therapeutic efficacy compared to that of SSPs in gut-related disorders and pathogen infections, which could be explained by an overall higher dosage (Chapman et al, 2011(Chapman et al, , 2012.…”
Section: Single-species and Multi-species Probioticmentioning
confidence: 99%
“…Bifidobacterium bifidum and L. acidophilus were often included in the formulation of MSPs to treat depressive symptoms in patients with MDD (Akkasheh et al, 2016;Bambling et al, 2017;Ghorbani et al, 2018) and other health conditions, such as polycystic ovarian syndrome, multiple sclerosis and IBS (Kouchaki et al, 2017;Ostadmohammadi et al, 2019;Zhang et al, 2019). Surprisingly, B. bifidum and L. acidophilus have not been tested independently for its antidepressive effect.…”
Section: Candidate Probiotics With Potential Antidepressive Effectmentioning
confidence: 99%
“…Familact (Zist Takhmir Co., Tehran, Iran) is a probiotic mixture supplement that has shown efficacy in several diseases . Therefore, we conducted this randomized crossover clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Familact (Zist Takhmir Co., Tehran, Iran) is a probiotic mixture supplement that has shown efficacy in several diseases. [13][14][15][16][17][18] Therefore, we conducted this randomized crossover clinical trial. The aim of this study was to assess the impact of add-on probiotic supplement on PAR symptoms and on the QoL of patients.…”
Section: Introductionmentioning
confidence: 99%